2011
DOI: 10.1074/jbc.m110.204602
|View full text |Cite
|
Sign up to set email alerts
|

A Multiprotein Binding Interface in an Intrinsically Disordered Region of the Tumor Suppressor Protein Interferon Regulatory Factor-1

Abstract: The interferon-regulated transcription factor and tumor suppressor protein IRF-1 is predicted to be largely disordered outside of the DNA-binding domain. One of the advantages of intrinsically disordered protein domains is thought to be their ability to take part in multiple, specific but low affinity protein interactions; however, relatively few IRF-1-interacting proteins have been described. The recent identification of a functional binding interface for the E3-ubiquitin ligase CHIP within the major disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 71 publications
4
35
0
Order By: Relevance
“…As mentioned above, the association of Wt-NPM1 and IRF-1 inhibits the DNA binding of IRF-1. Narayan et al showed that IRF1 binds directly to Wt-NPM1 through a short linear motif in the nuclear localization sequence outside the DNA-binding domain (31). These results suggest that the inhibition of DNA binding by NPM1 may not be through simple interference with the DNA-binding domain of MEF/ELF4.…”
Section: Discussionmentioning
confidence: 60%
“…As mentioned above, the association of Wt-NPM1 and IRF-1 inhibits the DNA binding of IRF-1. Narayan et al showed that IRF1 binds directly to Wt-NPM1 through a short linear motif in the nuclear localization sequence outside the DNA-binding domain (31). These results suggest that the inhibition of DNA binding by NPM1 may not be through simple interference with the DNA-binding domain of MEF/ELF4.…”
Section: Discussionmentioning
confidence: 60%
“…Mechanistically, the ability of IDPs to assume different conformations when interacting with different binding partners (Kriwacki et al, 1996;Tompa et al, 2005;Uversky et al, 2008;Narayan et al, 2011) may explain how multiple interactions can be accommodated by the relatively short TPs during binding and translocation. The kinetics of favorable recognition between two components may be accelerated by increasing the encounter productivity using the fly-casting model (Shoemaker et al, 2000), which proposes that TPs are rapidly recognized regardless of whether the peptide binds to the receptor with one topological orientation or the opposite.…”
Section: Discussion Flexible Recognition Of Tps By Toc34mentioning
confidence: 99%
“…CHIP, a U-box E3 ligase, docks to a multi-protein-binding interface in the intrinsically disordered Mf2 domain of IRF-1 and this interaction is required for efficient modification of IRF-1 by CHIP in cells [16]. Interestingly, a domain with homology with the Mf2 is involved in ubiquitination of IRF-2 ( Figure 1A), a close relative of IRF-1, by the RING E3 ligase MDM2 [30], suggesting that the Mf2 may comprise a general docking site for IRF-1 and IRF-2 E3 ligases.…”
Section: Mdm2 Can Act As An E3 Ligase For Irf-1 In Vitro and In Cellsmentioning
confidence: 99%
“…His-CHIP, His-UbcH5 and His-SET (pET-26b-SET was from J. Libermann and T. Tuschi via Addgene [18]) were purified using Ni-NTA (Ni 2 + -nitrilotriacetate) agarose (Qiagen) following the manufacturer's instructions. Kap-1 was purified as described previously [16] (pGEX-4T1-Kap-1 was a gift from Dr A. Ivanov, West Virginia University, Morgantown, West Virginia, U.S.A. [19]). Untagged p53 purified from insect cells was a gift from Dr Jennifer Fraser and Professor Ted Hupp (both from the University of Edinburgh, Edinburgh, Scotland, U.K.).…”
Section: Reagents Plasmids and Protein Preparationmentioning
confidence: 99%
See 1 more Smart Citation